Flaws of Article 9, 10, and 26 of the Criminal Act in South Korea and Possible Solutions - Kang, Chaerin (Technium Social Sciences Journal, 2020)
The purpose of this research paper is to underline a few of the problematic articles of the Criminal Act in Korea and suggest possible solutions. In the Republic of Korea, three criminal elements—Applicability of Constituent Requirements, Criminal Defences, and the Principle of Responsibility—must be proven to convict a defendant. When a perpetrator does not meet all three criminal elements, they are protected by particular articles of the Criminal Act such as Articles 9, 10, and 26. These articles guarantee citizens’ right to decide their own actions accordingly and provide an opportunity for improvement by reducing the punishment. All three articles of the Criminal Act reflect positive intentions embedded in the law. However, the articles’ flaws have begun to cause the perpetrators to exploit the law and disdain Korea’s Criminal Act. Thus, this paper aims to consider the Criminal Act’s malfunctions, especially within Article 9, 10, and 26, and suggest possible solutions to improve its shortages.